Zombie Apocalypse: Engaging Students In Environmental Health And Increasing Scientific Literacy Through The Use Of Cultural Hooks And Authentic Challenge Based Learning Strategies - Whiley, Harriet; Houston, Donald; Smith, Anna; Ross, Kirstin (Journal of University Teaching and Learning Practice, 2018)
Environmental Health (EH) is an essential profession for protecting human health and yet as a discipline it is under-recognised, overlooked and misunderstood. Too few students undertake EH studies, culminating in a dearth of qualified Environmental Health Officers (EHOs) in Australia. A major deterrent to students enrolling in EH courses is a lack of appreciation of the relevance to their own lives. This is symptomatic of a wider problem of scientific literacy: the relevance gap and how to bridge it. Employing a cultural hook offers a means to connect students to science and the fundamental elements of EH. Zombies feature prominently in the contemporary cultural landscape – movies, TV, gaming, music, cosplay, ‘Zombie Marches’. A Zombie Apocalypse provides an engaging platform to convey key EH concepts such as microbes and toxins, whilst improving the scientific literacy skills of both science and non-science students. Engaging students through this cultural hook bridged the relevance gap, connected students to science, and inspired an increased interest in EH.